2016
DOI: 10.1007/s00467-016-3337-1
|View full text |Cite
|
Sign up to set email alerts
|

Accentuated hyperparathyroidism in type II Bartter syndrome

Abstract: PTH, serum Pi levels, and urinary threshold for Pi reabsorption are significantly elevated in type II vs. type IV BS, suggesting a PTH resistance state. This may be a response to more severe long-standing hypercalciuria, leading to a higher rate of nephrocalcinosis in BS-II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…While the former were present, serum levels of magnesium were normal in this patient. High PTH levels, have been shown in a large cohort of patients with BS type 2, and attributed to persistent hypercalciuria [13].…”
Section: Discussionmentioning
confidence: 95%
“…While the former were present, serum levels of magnesium were normal in this patient. High PTH levels, have been shown in a large cohort of patients with BS type 2, and attributed to persistent hypercalciuria [13].…”
Section: Discussionmentioning
confidence: 95%
“…-Further studies are necessary to understand the pathophysiology of these abnormalities and to demonstrate whether PTH and/or phosphate should be a treatment target in these salt- In recent years, several investigators have observed abnormal levels of parathyroid hormone (PTH) and serum phosphate in patients with Bartter and Gitelman syndrome [3][4][5][6][7][8][9][10][11][12][13] . Patients with Bartter syndrome tend to have a high PTH [3][4][5][6][7][8][9] . However, the prevalence and pathophysiology of hyperparathyroidism in these Bartter patients are unclear.…”
Section: What Impact This May Have On Practice or On Policy?mentioning
confidence: 99%
“…Bartter syndrome 3,5 . In patients with Gitelman syndrome, high PTH levels have only been described in patients that had parathyroid adenoma 14,15 , while hypophosphatemia has been reported in several small studies [10][11][12][13] and has been attributed to renal phosphate wasting 12,13 .…”
Section: What Impact This May Have On Practice or On Policy?mentioning
confidence: 99%
See 2 more Smart Citations